P46 Cigarette smoke- and hypoxia-induced imbalanced vasoactive gene expression in human pulmonary artery endothelial and smooth muscle cells. (15th November 2017) - Alqarni, A; Brand, O; Pasini, A; Alshehri, M; Pang, L
Abstract : Background: Pulmonary Hypertension (PH) is a common and serious complication of Chronic Obstructive Pulmonary Disease (COPD) associated with increased mortality and morbidity and characterised by Pulmonary Artery Smooth Muscle Cell (PASMC) hyperproliferation and vascular remodelling. Studies suggest that chronic hypoxia and Cigarette Smoke (CS) can cause aberrant PASMC proliferation and vascular remodelling, however, how cigarette smoke and hypoxia contribute to pulmonary artery wall thickening and PH in COPD is not fully understood. We hypothesise that hypoxia and CS can induce an imbalance between excessive vasoconstrictors and deficient vasodilators, which then contribute to aberrant PASMC proliferation in COPD-associated PH and can be a target for therapeutic intervention. Method: To prove the hypothesis, confluent Human Pulmonary Artery Smooth Muscle Cells (hPASMCs) and Human Pulmonary Artery Endothelial Cells (hPAECs) were treated with different concentrations of Cigarette Smoke Extract (CSE) (1%, 2.5%, and 5%) under normoxic (21% O2 ) or hypoxic (1% O2 ) condition for 72 hour. The protein and mRNA expression of Prostacyclin Synthase (PGIS), Cyclooxygenase-2 (COX-2), Endothelial Nitric Oxide Synthase (eNOS), Thromboxane A Synthase (TXAS), and Endothelin 1(ET-1) was analysed by Western blotting and real-time RT-PCR, respectively. Results: The expression of vasodilator genes eNOS and PGIS was noticeably downregulated in both hPASMCs and hPAECs, whereas TXAS and COX-2 expression was markedly induced by CSE and hypoxia, either individually or in combination in both hPASMCs and hPAECs. ET-1 expression was increased by CSE and hypoxia in hPAECs. Interestingly, ET-1 was upregulated by hypoxia, but reduced by CSE, with a net increase when both were combined in hPASMCs. Conclusion: These findings support our hypothesis that CS and hypoxia can cause an imbalance between excessive vasoconstrictors and deficient vasodilators in hPASMC and hPAECs. This imbalance may eventually lead to aberrant PASMC proliferation and vascular remodelling in COPD-associated PH. Further experiments are being conducted to confirm this by analysing vasoactive gene expression and mediator release in both hPASMCs and hPAECs. Our findings also pave the way for further studies on cellular functions and intervention drug effects.